Digital Financial Strategies in Managing SMEs to Maximize Profitability - Alamsyah, Wahyu; Yulianti, Rahmah; Khairuna, Khairuna; Nurhayati, Rasyedia; Masyitah, Masyitah (LPPM STIKI Malang, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy. However, they continue to face significant challenges in financial management. Key issues include a lack of financial literacy, manual record-keeping prone to errors, limited access to formal financial services, and minimal adoption of digital technology. These obstacles often lead to operational inefficiencies, data-less decision-making, and low market competitiveness. Digital financial solutions emerge as innovative tools to address these challenges. By leveraging digital technology, MSMEs can enhance operational efficiency, accelerate transactions, support strategic decision-making, and improve access to formal financial services. This article explores various benefits of digital financial solutions, ranging from financial transparency and cost savings to the potential for significantly increasing profitability. Additionally, the article presents practical and relevant digitalization strategies for MSMEs, including step-by-step adoption approaches and case studies of successful MSMEs that have embraced technology. Through the use of illustrations such as graphics, flowcharts, and real-world examples, this article aims to provide actionable and inspiring insights for MSME players in optimizing digital finance. By doing so, MSMEs can achieve sustainable business practices and improve competitiveness in the digital economy era.